Best Answer

4 (apples) plus 3 (apples) = 7 (apples).

4 (cows) + 3 (cows) = 7 (cows)

4 (x2y) + 3 (x2y) = 7 (x2y)

Q: What is 4x squared y plus 3x squared y?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

y=xsquared-4x+2

4x+3y = 12 3y = -4x+12 y = -4/3x+4

since y = 3x+1 we have y squared =(3x+1) squared x^2 + y^2 = 25 x^2 + (3x+1)^2=25 x^2 + 9x^2+ 6x+1 = 25 10x^2 + 6x + 1 = 25 10x^2 + 6x -24 = 0 solve x from quadratic formula x = 1.28 y = 3x + 1 = 4.83

y=3x+3 -- This could be the formula for a line, where the slope is 3 and the y intercept is (0,3). In the next line the slope would be 4 and the y-intercept would be 5

If you mean: 3x+4y = 12 then y = -3/4x+3 whereas -3/4 or -0.75 is the slope and 3 is the y intercept

Related questions

(3x - y+ 2)(3x + y + 2)

3x + y

(3x + 3y)(x + y) = 3(x + y)2

If: y = 4x2-2x-1 and y = -2x2+3x+5 Then the length of the line works out as: 65/18 or 3.6111 ... recurring decimal 1

-6 + 3x - y - 4x + 4y + 5 (combine like terms) = (-6 + 5) + (3x - 4x) + (-y + 4y) = -1 - x + 3yHope this helps :)

It is equivalent to x + y + 4.

y=xsquared-4x+2

3x + 5 + x + 10 + 2y 4x + 2y + 15 |:2 2x + y + 7.5 2x + y + 7.5 is equivalent to the original.

y = 3x + 21x2 = 3x(1 + 7x)

9x2 - 6xy + y2 - 81 = (3x - y)2 - 81 = (3x - y - 9)*(3x - y + 9)

If: y = 4x^2 -2x -1 and y = -2x^2 +3x +5 Then: 4x^2 -2x -1 = -2x^2 +3x +5 Transposing terms: 6x^2 -5x -6 = 0 Factorizing: (3x+2)(2x-3) = 0 => x = -2/3 or x = 3/2 By substitution the points of contact are at: (-2/3, 19/9) and (3/2, 5)

If: y = 4x^2 -2x -1 and y = -2x^2 +3x+5 Then: 4x^2 -2x-1 = -2x^2 +3x+5 or 6x^2 -5x -6 = 0 Factorizing the above: (3x+2)(2x-3) = 0 meaning x = -2/3 or x = 3/2 By substitution points of contact are at: (-2/3, 19/9) and (3/2, 5)